«Solamente está sujeta al marido la que sin dote se recibe» La dote canónica y la mujer casada en la tradición legal hispánica - Martín-Humanes, José-María (2023)
"Dowry" is a common word in popular use in the Hispanic world. Our forebears used it often, to denote the set of assets a woman brought with her to the marriage. However, the reality of this historical reality becomes more complex as one’s focus narrows and enters the legal sphere. This text offers a technical reading of the issue based on the doctrinal corpus and legal resources from the late Medieval and Earl Modern Eras (13th- 18th centuries). The aim is to contribute to a general understanding of the dowry in the framework of the Hispanic legal tradition, concentrating on the regulatory dimension of the phenomenon and on its interpretation and application in legal praxis. Nevertheless, the importance of local legislation in the territories governed by the Spanish monarchy, as well as of usage and custom, signal the extensive work still to be done in this regard.
Keywords: Baja Edad Media; Derecho Canónico; Dote; Edad Moderna; Monarquía Hispánica